Mosaic trisomy 16 at amniocentesis in a pregnancy associated with positive non-invasive prenatal testing for trisomy 16, placental trisomy 16, intrauterine growth restriction, intrauterine fetal death, cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, and prenatal progressive decrease of the aneuploid cell line - Chih-Ping Chen; Fang-Tzu Wu; Yi-Yung Chen; Yen-Ting Pan; Peih-Shan Wu; Meng-Shan Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2023)
Objective: We present mosaic trisomy 16 at amniocentesis in a pregnancy associated with positive non-invasive prenatal testing (NIPT) for trisomy 16, placental trisomy 16, intrauterine growth restriction (IUGR), intrauterine fetal death (IUFD), cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes and uncultured amniocytes, and prenatal progressive decrease of the aneuploid cell line. Case report: A 26-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of positive NIPT for trisomy 16 at 12 weeks of gestation. Amniocentesis revealed a karyotype of 47,XX,+16 [10]/46,XX[17], and simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (16) × 3 [0.43] consistent with 43% mosaicism for trisomy 16. She was referred for genetic counseling at 19 weeks of gestation, and a fetus with IUGR was noted to have a size equivalent to 16 weeks of gestation. At 23 weeks of gestation, the fetus manifested oligohydramnios, fetal cardiomegaly and severe IUGR (fetal size equivalent to 20 weeks of gestation). Repeat amniocentesis revealed a karyotype of 46,XX (20/20 colonies) in cultured amniocytes and mosaic trisomy 16 by aCGH in uncultured amniocytes. aCGH analysis on uncultured amniocytes revealed the result of arr 16p13.3q24.3 × 2.3, consistent with 30% (log2 ratio = 0.2) mosaicism for trisomy 16. Quantitative fluorescence polymerase chain reaction (QF-PCR) assays on the DNA extracted from parental bloods and uncultured amniocytes excluded uniparental disomy (UPD) 16. The parental karyotypes were normal. IUFD was noted at amniocentesis. The pregnancy was subsequently terminated, and a 288-g female fetus was delivered with no phenotypic abnormalities. The umbilical cord had a karyotype of 46,XX (40/40 cells), and the placenta had a karyotype of 47,XX,+16 (40/40 cells). QF-PCR assays of the placenta confirmed a maternal origin of trisomy 16. Conclusion: Mosaic trisomy 16 at amniocentesis can be associated with positive NIPT for trisomy 16, placental trisomy 16, IUGR, IUFD, cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, and prenatal progressive decrease of the aneuploid cell line.